2017
DOI: 10.1016/j.brainres.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 modulation of NF-κB signaling in astrocytes is independent of its ability to mediate astrocytic viability in ischemic injury

Abstract: Transglutaminase 2 (TG2) is a multifunctional protein that can contribute to cell death and cell survival processes in a variety of disease contexts. Within the brain, TG2 has been shown to promote cell death in ischemic injury when expressed in astrocytes (Colak and Johnson, 2012). However, the specific functions and characteristics of astrocytic TG2 that mediate this effect are largely unknown. Therefore, the goal of this study was to investigate the role of astrocytic TG2 in mediating cellular viability pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…Primary cortical astrocytes were harvested at P0 from mice as previously described [2,10]. Astrocytes were maintained in MEM media supplemented with 10% FBS, 6 g/L glucose, 1 mM sodium pyruvate, and 25 μg/mL Gentamicin (Glia MEM) prior to use in experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary cortical astrocytes were harvested at P0 from mice as previously described [2,10]. Astrocytes were maintained in MEM media supplemented with 10% FBS, 6 g/L glucose, 1 mM sodium pyruvate, and 25 μg/mL Gentamicin (Glia MEM) prior to use in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The astrocyte cultures are maintained in serum and passaged once before being used. This results in cultures that contain >95% astrocytes [2,10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When astrocytes were cocultured with neurons it was found that TG2–/– astrocytes were able to protect wild‐type or TG2–/– neurons from OGD‐induced cell death to a significantly greater extent than wild‐type astrocytes (Colak & Johnson, ). In further studies, it was also found that knocking down TG2 in astrocytes with TG2 shRNA also significantly increased their viability following OGD (Feola et al, ) and their ability to protect neurons. While further investigation is needed, one possible explanation for this phenomenon could be that TG2 knockout in astrocytes could result in changes in the metabolic pathways that produce products that are released to protect neurons.…”
Section: The Relationship Between Tg2 Localization Activation Statementioning
confidence: 99%
“…Whether TG2 is beneficial or detrimental to cell survival is dependent on the cell type and stressors. In astrocytes, TG2 facilitates ischemic cell death as TG2 deletion or knockdown supports survival in an oxygen and glucose deprivation (OGD) paradigm (Colak & Johnson, ; Feola, Barton, Akbar, Keillor, & Johnson, ). In contrast to its detrimental role in astrocytes, TG2 supports neuron survival.…”
Section: Introductionmentioning
confidence: 99%